Excess cerebellar granule neurons induced by the absence of p75NTR during development elicit social behavior deficits in mice - Zanin, Juan Pablo; Pandya, Mansi A.; Espinoza, Diego; Friedman, Wilma J.; Shiflett, Michael W. (Frontiers in Molecular Neuroscience, 2023)
Recently the cerebellum has been associated with non-motor functions, including cognitive and emotional behavior. Anatomical and functional studies demonstrate bidirectional cerebellar connections with brain regions involved in social cognition. Cerebellar developmental abnormalities and injury are often associated with several psychiatric and mental disorders including autism spectrum disorders and anxiety. The cerebellar granule neurons (CGN) are essential for cerebellar function since it provides sensorimotor, proprioceptive, and contextual information to Purkinje cells to modify behavior in different contexts. Therefore, alterations to the CGN population are likely to compromise cerebellar processing and function; however, the specific role for CGNs in non-motor functions is not fully understood. Previously we demonstrated that the p75 neurotrophin receptor (p75NTR) was fundamental for the development of the CGN. In the absence of p75NTR, we observed increased proliferation of the granule cell precursors (GCP), followed by increased GCP migration toward the internal granule layer. The excess granule cells were incorporated into the cerebellar network, inducing alterations in cerebellar circuit processing. In the present study, we used two conditional mouse lines to specifically delete the expression of p75NTR. In both mouse lines, deletion of the target gene was under the control of the transcription factor Atoh-1 promotor, however, one of the lines was also tamoxifen inducible. We observed loss of p75NTR expression from the GCPs in all cerebellar lobes. Compared to WT animals, both mouse lines exhibited reduced preference for social interactions when presented with a choice to interact with a mouse or object, and reduced preference for social novelty when presented with a novel or familiar conspecific mouse. Open field locomotor behavior and operant reward learning were unaffected in both lines. Increased anxiety-related behavior in the elevated zero maze was present in mice with constitutive p75NTR deletion; however, this effect was not present in the tamoxifen inducible mice with p75NTR deletion that more specifically targeted the GCPs. Our findings contribute to the increasing evidence that the cerebellum can support non-motor-related behaviors, including social behavior.